CONFLICTS AND SEGREGATION OF HOUSING CLUSTER COMMUNITIES AND ITS SURROUNDING - Pitri Yandri (Research Centre for Population, Indonesian Institute of Sciences, 2015)
Since it was first studied by Leicsh (2002), the phenomenon of housing cluster in Indonesia has changed significantly. Fourteen years have changed everything, and these changes are caused by local governments. Now, developers are more inclined and prefer to build a housing cluster, and tragically it is located in the middle of local neighborhoods. In this case, gated communities are more apparent than fourteen years ago. Through the Mann Whitney U test, it turns out that there is dissimilarity among people in the housing cluster with people in the local neighborhood, and it has even shown a confrontational conflict. The issues of the conflict revolve around conflict of interest, access-to and use-off the road. At the same time, people in the housing cluster and local neighborhood are segregated. Segregation in Indonesia occurs in both areas with different tension. However, voluntary and involuntary segregation could not fully answer the case of residential segregation in the suburb of this country. Hence, segregation is created not because of the preferences of people in both areas, but y and for an economic and social system of development policy. Using Critical Discourse Analysis, this paper demonstrates the emergence of new patterns of residential segregation, namely systemic spatial segregation.Keywords: Housing, Gated Communities, Housing Cluster, Segregation, Systemic Spatial Segregation